Multi-principal-element low-modulus Ti-Zr-based medium-entropy alloy and preparation method thereof
By introducing Nb, Ta, and Hf elements into Ti50Zr50 alloy and adjusting the mixing entropy and valence electron concentration, a multi-principal-component low-modulus Ti-Zr-based medium-entropy alloy was prepared, which solved the problems of high elastic modulus and adverse reactions of existing bioimplant materials and achieved biomedical materials with low modulus, high ductility, and biocompatibility.
Patent Information
- Application Number
- CN202511079549.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-09-05
- Estimated Expiration
- 2045-08-04
AI Technical Summary
Existing bio-implantable metal materials have problems such as high elastic modulus, adverse reactions and high cost, which makes it difficult to meet the requirements of low modulus, high ductility and biocompatibility for biomedical materials.
By introducing Nb, Ta and Hf elements on the basis of Ti50Zr50 alloy, adjusting the mixing entropy and valence electron concentration, a multi-principal component low modulus Ti-Zr based medium entropy alloy with the composition of (TiZr)100-10xNb4xTa4xHf2x was designed. It was prepared by vacuum melting and multi-pass hot rolling process, and the hot rolling temperature and deformation amount were controlled to obtain a single β phase structure.
It achieves low elastic modulus, excellent toughness and biocompatibility, reduces stress shielding effect, and broadens the application scenarios of biomedical materials.
Smart Images

Figure CN120591612A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of alloy materials, and in particular to a multi-principal-element low-modulus Ti-Zr-based medium-entropy alloy and a preparation method thereof. Background Art
[0002] With the advancement of biomedicine and materials science, bioimplant metals are increasingly demanding non-toxicity, low modulus, and high ductility. Current bioimplant metals in clinical use have several drawbacks. For example, stainless steel releases nickel ions from wear and corrosion, which can cause adverse reactions such as allergies, inflammation, or cell damage, with an incidence rate of up to 10-15%. Ti-6Al-4V alloy, a currently predominant bioimplant material, offers excellent processing properties but contains harmful elements such as aluminum (which poses a neurotoxic risk) and vanadium (which has a cytotoxic LD50 of less than 50 mg / kg). Long-term wear of cobalt-based alloy implants in the body can lead to the dissolution of cobalt and nickel ions. Cobalt ion release exceeding 0.1 ppm can cause localized tissue necrosis. Furthermore, the elastic modulus of traditional titanium alloys, such as stainless steel, Ti-6Al-4V alloy, and cobalt-based alloys, ranges from 110 to 210 GPa, significantly higher than the 20 to 40 GPa of cortical bone, potentially leading to stress shielding.
[0003] Relevant research has shown that biocompatible elements such as Ti, Zr, Hf, Nb, Ta, and Mo pose minimal risk to the human body. Therefore, alloys containing only these highly biocompatible elements are ideal biomedical materials and have garnered widespread attention from materials scientists, clinicians, and medical device manufacturers. In recent years, the thermodynamically high entropy effect, kinetically slow diffusion effect, structural lattice distortion effect, and performance cocktail effect of high-entropy alloys have provided new insights into the design of biomedical materials. Through rational compositional design, high-entropy alloys can exhibit the performance requirements of low elastic modulus and high elongation, potentially expanding their applications in the biomedical field.
[0004] Chinese patent application No. 202410394726.1 discloses a low modulus and high ductility Ti-Zr high entropy alloy and its preparation method and application. The general formula of the high entropy alloy is (TiZr) x M y (atomic percentage), wherein x ranges from 40 to 49, y ranges from 0.66 to 6.66, M represents Nb, Ta, and Mo elements, and the elastic modulus of the alloy is 83 to 100 GPa; the elastic modulus of the Ti-Zr high-entropy alloy is still relatively high, and the alloy is smelted without considering the intermediate alloy, requiring at least 10 smeltings to ensure compositional uniformity, and the smelting process is complicated.
[0005] Chinese patent application No. 201910842006.6 discloses a biomedical Ti-Zr-Hf-Nb-Ta high entropy alloy, the general formula of which is Ti a Zr b Hf c Nb d Ta e (atomic percentage), where 5≤a≤40, 5≤a≤40, 5≤a≤40, 5≤a≤40, 5≤a≤40, and a+b+c+d+e=100. Although the elastic modulus of the high-entropy alloy is as low as 54 GPa, the elongation of the alloy is less than 6%. In addition, when the content of Hf, Nb, and Ta is too high, the cost of the alloy will also be high.
[0006] Compared with Ti6Al4V, Ti 50 Zr 50 Binary alloys have a lower elastic modulus. Their stable phase at low temperatures is the α phase, with an elastic modulus of 86-114 GPa, which is still much higher than the 20-40 GPa of human bones. In contrast, Ti 50 Zr 50 The elastic modulus of the β phase in the binary alloy is lower than that of the α phase, but the β phase is only a stable phase at high temperatures. 50 Zr 50 Taking binary alloy as a model, by adding biocompatible elements such as Hf, Nb, Ta, and Mo, the β phase of the alloy is expanded, and by controlling the mixing entropy and valence electron concentration of the alloy, the elastic modulus of the alloy is reduced; by designing the content of alloying elements, it is of great significance to design Ti-Zr-Nb-Ta-Hf biomedical medium-entropy alloys with excellent performance. Summary of the Invention
[0007] In response to the defects existing in the prior art, the purpose of the present invention is to provide a multi-principal component low-modulus Ti-Zr-based medium-entropy alloy and a preparation method thereof. Based on the synergistic effect between TiZr alloy and Hf, Nb, and Ta alloys, by controlling the alloy molar ratio between the two, the mixing entropy and valence electron concentration of the alloy are improved, the β-phase forming ability is enhanced, the elastic modulus of the alloy is reduced, and the ductility of the alloy is improved, thereby expanding the application scenarios of the alloy material.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions: The first aspect of the present invention provides a multi-principal element low modulus Ti-Zr based medium entropy alloy, the composition of which is (TiZr) in atomic percentage 100-10x Nb 4x Ta 4x Hf 2x , where 1≤x≤4.
[0009] Preferably, the multi-principal element low modulus Ti-Zr based medium entropy alloy is (TiZr) 90 Nb4Ta4Hf2、(TiZr) 80 Nb8Ta8Hf4、(TiZr) 70 Nb 12 Ta 12 Hf6、(TiZr) 60 Nb 16 Ta 16 At least one of Hf8.
[0010] Preferably, the multi-principal element low modulus Ti-Zr based medium entropy alloy has a single-phase body-centered cubic crystal structure, and its microstructure is a single β phase.
[0011] Preferably, the mixing entropy of the multi-principal element low modulus Ti-Zr based medium entropy alloy is 1R~1.6R, and the valence electron concentration is 4~4.5.
[0012] Preferably, the elastic modulus of the multi-principal element low modulus Ti-Zr based medium entropy alloy is 65~90 GPa, the yield strength is 350~700 MPa, the tensile strength is 730~1000 MPa, and the elongation is 9.5%~25%.
[0013] The present invention uses Ti in an equal molar ratio 50 Zr 50 The binary alloy is a model alloy, with the valence electron concentration of Ti and Zr being 4. The alloy's mixing entropy and valence electron concentration can be adjusted by adjusting the valence electron concentration, thereby adjusting the ductility of the medium-entropy alloy. Furthermore, Nb, Ta, and Hf are all β-stabilizing elements, enabling the design of low-elastic-modulus β-titanium alloys. This can also achieve higher strength through lattice distortion, resolving the problem of existing medium-entropy alloys being unable to achieve a lower elastic modulus and a matching strength-toughness performance.
[0014] The above multi-principal low modulus Ti-Zr based medium entropy alloy has a simple body-centered cubic crystal structure, and the medium entropy alloy has a single β phase structure. The high entropy effect and high valence electron concentration synergistically enhance the β phase formation ability, and the alloy has excellent strength and toughness matching performance. 50 Zr 50 The alloy and the deficiency of high elastic modulus of traditional alloys provide new composition options for biomedical low modulus implant materials, meeting the urgent demand of biological implants for biocompatible and low elastic modulus metal materials.
[0015] The present invention is achieved by 50 Zr 50 The alloy is based on Nb, Ta and Hf elements, which can achieve the following goals: (1) Ti 50 Zr 50 The mixing entropy of the alloy is only 0.7R. By adding Nb, Ta and Hf elements, the mixing entropy of the alloy can be increased to between 1R and 1.6R, forming a medium-entropy alloy and avoiding the tendency to form intermetallic compounds; (2) Nb, Ta, and Hf are all β-stabilizing elements, and the high valence electron concentration can form a single β phase, which reduces the elastic modulus and ultimately forms a medium-entropy alloy with low elastic modulus and excellent toughness. Its biocompatibility is far superior to the currently used Ti-6Al-4V, stainless steel, and cobalt-based alloys. At the same time, the low elastic modulus can reduce the stress shielding effect. (3) The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy is (TiZr) in atomic percentage 100- 10x Nb 4x Ta 4x Hf 2x Within a certain atomic percentage range, as the atomic percentage of Nb-Ta-Hf increases, the alloy's mixing entropy and valence electron concentration increase, leading to a gradual increase in the yield strength and tensile strength of the medium-entropy alloy, while the elongation gradually decreases. Beyond a certain atomic percentage range, the toughness of the medium-entropy alloy deteriorates. Furthermore, increasing the atomic percentage of Nb-Ta-Hf significantly increases the alloy's cost. In summary, a value of x of 1 ≤ x ≤ 4 is most suitable.
[0016] The preparation method of the multi-principal component low modulus Ti-Zr-based medium-entropy alloy of the present invention is to prepare the multi-principal component low modulus Ti-Zr-based medium-entropy alloy through a vacuum melting process and multiple hot rolling treatments. The whole process is relatively simple. The above-mentioned multi-principal component low modulus Ti-Zr-based medium-entropy alloy can meet the urgent needs of biological implants for biocompatibility and low elastic modulus metal materials, and provides a new direction for the preparation of medium-entropy alloy materials for biological implants.
[0017] The second aspect of the present invention provides a method for preparing the multi-principal element low modulus Ti-Zr based medium entropy alloy as described in the first aspect of the present invention, comprising the following steps:
[0018] S1, after pre-treating the Ti, Zr, Nb, Ta, and Hf metal raw materials, converting the atomic percentage of the Ti-Zr-based entropy alloy into mass percentage, and then weighing each metal raw material;
[0019] S2, performing a first vacuum melting of the Nb, Ta, and Hf metal raw materials to obtain a NbTaHf master alloy ingot;
[0020] S3, vacuum melting the Ti metal raw material and the NbTaHf master alloy ingot three times to obtain a NbTaHfTi master alloy ingot;
[0021] S4, the Zr metal raw material and the NbTaHfTi master alloy ingot are vacuum melted for the fifth time to obtain (TiZr) 100-10x Nb 4x Ta 4x Hf 2x Alloy ingot, where 1≤x≤4;
[0022] S5, (TiZr) 100-10x Nb 4x Ta 4x Hf 2x The alloy ingot is vacuum melted for the sixth time. After melting, the alloy melt is cast into a water-cooled copper mold. After cooling, a uniform composition (TiZr) is obtained. 100-10x Nb 4x Ta 4x Hf 2x alloy ingots;
[0023] S6, the (TiZr) obtained in step S5 100-10x Nb 4x Ta 4x Hf 2x The alloy ingot is processed into an alloy plate after cooling, and then the alloy plate is subjected to multiple hot rolling treatments at high temperature. After each hot rolling treatment, it is cooled with water to obtain a multi-principal element low modulus Ti-Zr based medium entropy alloy.
[0024] Preferably, in step S1, the pretreatment includes acid washing, ethanol washing under ultrasonic conditions, and vacuum drying.
[0025] Preferably, in step S1, the Ti, Zr, Nb, Ta, and Hf metal raw materials are all metal single-substance particles, the purity of the metal single-substance particles is ≥99.5%, and the size of the metal single-substance particles is 2-10 mm.
[0026] Preferably, during the vacuum melting process in steps S2 to S5, a magnetic levitation induction melting furnace is used, the voltage of the magnetic levitation induction melting furnace is controlled to be 360 to 550 V, the current is 450 to 480 A, the time of each melting is 15 to 20 min, the melting vacuum is 0.016 to 0.02 Pa, and the argon filling pressure is -0.06 to 0 Pa.
[0027] Preferably, in step S2, the atomic percentage of the NbTaHf master alloy ingot is Nb2Ta2Hf1. Preferably, the specific process of step S3 is as follows:
[0028] Ti metal raw materials were divided into three batches according to mass percentage: 8-15%, 20-25% and 60-72%;
[0029] The Ti metal raw material containing 8-15% and the NbTaHf master alloy ingot are vacuum melted for the second time to obtain a master alloy ingot A;
[0030] The 20-25% Ti metal raw material and the master alloy ingot A are vacuum melted for the third time to obtain the master alloy ingot B;
[0031] The remaining 60-72% of the Ti metal raw material and the master alloy ingot B are vacuum melted for the fourth time to obtain a NbTaHfTi master alloy ingot.
[0032] The present invention uses a vacuum melting process to quickly obtain medium-entropy alloy samples of different proportions, and then screens the high-entropy alloy samples according to the comprehensive performance threshold, thereby determining the optimal element ratio and optimal process parameters in the medium-entropy alloy, greatly shortening the optimization cycle of the high-entropy alloy, and thus quickly and accurately obtaining products with excellent performance; combined with Figure 1 As shown, the present invention adopts six vacuum melting processes, and vacuum melts five metal raw materials of Ti, Zr, Nb, Ta, and Hf in batches. Since the melting points of Nb (melting point 2468°C), Ta (melting point 2996°C), and Hf (melting point 2227°C) are relatively high and close to each other, the first vacuum melting process is used to obtain the Nb2Ta2Hf master alloy ingot. The melting point of the Ti metal raw material is the lowest (Ti melting point 1668°C), and the Ti metal raw material is gradually melted three times (the Ti metal raw material is divided into three batches by mass percentage: 8-15%, 20-25%, and 60-72%), and then the Zr metal raw material (Zr melting point 1852°C) is melted. After all the metal raw materials are melted, the TiZr is melted again (TiZr). 100- 10x Nb 4x Ta 4x Hf 2x Alloy ingots are cast, and ultimately the melting point of the alloy is gradually lowered to obtain alloy ingots with uniform chemical composition.
[0033] Preferably, in step S6:
[0034] The thickness of the alloy plate is 10-30 mm;
[0035] During the multi-pass hot rolling process, the hot rolling temperature is 700-900° C., the total hot rolling deformation is 70%-90%, and the pressing amount of each pass is 1.0-2.0 mm.
[0036] The preparation method of the present invention significantly influences the properties of the final alloy, particularly the hot rolling temperature and deformation conditions, which significantly affect the mechanical properties of the medium-entropy alloy. During the hot rolling process, the temperature is controlled between 700°C and 900°C, and the total deformation is controlled between 70% and 90%. This can regulate the grain size and recrystallization behavior of the alloy, thereby affecting its mechanical properties.
[0037] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is based on the synergistic effect between TiZr alloy and Nb, Ta, and Hf components. By controlling the alloy molar ratio between the two, the thermodynamic parameters and mechanical properties of the medium-entropy alloy are regulated. On the one hand, the biocompatibility of the alloy material is guaranteed and the β phase region is expanded. On the other hand, the elastic modulus of the alloy is effectively reduced and the ductility of the alloy is improved, which makes up for the shortcomings of the comprehensive mechanical properties of existing alloys. It provides a new component selection for bioimplant metal materials and meets the urgent demand for non-toxic, low-modulus alloy materials for biomedical implants. 2. The present invention uses an equal molar ratio of Ti 50 Zr 50 The binary alloy is a model alloy. The valence electron concentration of Ti and Zr is 4. By adding Nb, Ta, and Hf elements, the mixing entropy and valence electron concentration of the alloy are adjusted. By adjusting the valence electron concentration of the alloy, the ductility of the medium-entropy alloy is adjusted. In addition, Nb, Ta, and Hf are all β-stabilizing elements, which can be used to design low-elastic modulus β titanium alloys, achieving higher strength through lattice distortion. 3. The present invention designs the atomic percentage of the alloy, uses multiple vacuum melting processes and multiple hot rolling passes, and controls the hot rolling temperature and deformation to prepare a medium-entropy alloy material with low elastic modulus and single β phase, which has good toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Flowchart of the preparation method of the multi-principal element low modulus Ti-Zr based medium entropy alloy of the present invention;
[0039] Figure 2 The multi-principal element low modulus Ti-Zr based medium entropy alloy (TiZr) prepared in Example 1 of the present invention 90 Microstructure diagram of Nb4Ta4Hf2;
[0040] Figure 3 The multi-principal element low modulus Ti-Zr based medium entropy alloy (TiZr) prepared in Example 4 of the present invention 90 Microstructure diagram of Nb4Ta4Hf2;
[0041] Figure 4 The multi-principal element low modulus Ti-Zr based medium entropy alloy (TiZr) prepared in Example 5 of the present invention90 Microstructure diagram of Nb4Ta4Hf2. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below with reference to specific examples. The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.
[0043] The raw materials used in the following examples and comparative examples are all metal raw materials with a purity of ≥99.95% and a particle size of 2-10 mm.
[0044] Example 1
[0045] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0046] Step 1: Before smelting, the Ti, Zr, Nb, Ta and Hf metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively.
[0047] Step 2: Press (TiZr) 90 The atomic percentage of Nb4Ta4Hf2 is converted into mass percentage, and the clean metal elements of Ti, Zr, Nb, Ta and Hf are accurately weighed to the nearest 0.1 mg.
[0048] Step 3: Place the Nb, Ta and Hf metal raw materials in a magnetic levitation induction melting furnace for the first vacuum melting. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain a Nb4Ta4Hf2 master alloy ingot.
[0049] Step 4: Place the Nb4Ta4Hf2 master alloy ingot and 10% Ti metal raw material in a magnetic levitation induction melting furnace for a second vacuum melting. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain Ti 5.5 Nb4Ta4Hf2 master alloy ingot (i.e. master alloy ingot A).
[0050] Step 5: Ti 5.5 The Nb4Ta4Hf2 master alloy ingot and 20% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the third vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 16.5 Nb4Ta4Hf2 master alloy ingot (i.e., master alloy ingot B).
[0051] Step 6: Ti 16.5The Nb4Ta4Hf2 master alloy ingot and the remaining 70% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the fourth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 45 Nb4Ta4Hf2 master alloy ingot (i.e., NbTaHfTi master alloy ingot).
[0052] Step 7: Ti 45 The Nb4Ta4Hf2 master alloy ingot and all Zr metal raw materials are placed in a magnetic levitation induction melting furnace for the fifth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain (TiZr) 90 Nb4Ta4Hf2 alloy ingot.
[0053] Step 8: (TiZr) 90 The Nb4Ta4Hf2 alloy ingot was placed in a magnetic levitation induction melting furnace for the sixth vacuum melting. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a uniform composition (TiZr) 90 Nb4Ta4Hf2 alloy ingot.
[0054] During the above six vacuum melting processes, the voltage of the magnetic levitation induction melting furnace was controlled to be 360V, the current was 450A, the time of each melting was 20min, the melting vacuum was 0.016Pa, and the argon filling pressure was -0.06Pa.
[0055] Step 9: The alloy ingot obtained in step 8 is processed into 10 mm thick discs by wire cutting; then hot rolling is performed at 700 ° C, using multiple hot rolling processes with a total deformation of 80% and a pressing amount of 1.0 mm each time. After the hot rolling, water is used for cooling to obtain (TiZr) 90 Nb4Ta4Hf2 medium entropy alloy.
[0056] (TiZr) in this embodiment 90 The Nb4Ta4Hf2 medium entropy alloy has a single-phase body-centered cubic crystal structure. Its microstructure is shown in Figure 2 As shown, the microstructure is a single β phase.
[0057] (TiZr) in this embodiment 90 The arithmetic mean grain size of the Nb4Ta4Hf2 medium entropy alloy is 56µm, and the area-weighted mean grain size is 98µm. -4 / s strain rate test, the results show that the elastic modulus is 73GPa, the yield strength is 391 MPa, the tensile strength is 800MPa, and the elongation is 21%. 90The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0058] Example 2
[0059] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 70 Nb 12 Ta 12 Hf6, wherein each element is expressed in atomic percentage.
[0060] Step 1: Before smelting, the Ti, Zr, Nb, Ta and Hf metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively.
[0061] Step 2: Press (TiZr) 70 Nb 12 Ta 12 The atomic percentage of Hf6 is converted into mass percentage, and the cleaned metal elements of Ti, Zr, Nb, Ta and Hf are accurately weighed to the nearest 0.1 mg.
[0062] Step 3: Place the Nb, Ta and Hf metal raw materials in a magnetic levitation induction melting furnace for the first vacuum melting. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain Nb 12 Ta 12 Hf6 master alloy ingot.
[0063] Step 4: Nb 12 Ta 12 The Hf6 master alloy ingot and 10% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for a second vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti. 3.5 Nb 12 Ta 12 Hf6 master alloy ingot.
[0064] Step 5: Ti 3.5 Nb 12 Ta 12 The Hf6 master alloy ingot and 20% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the third vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 10.5 Nb 12 Ta 12 Hf6 master alloy ingot.
[0065] Step 6: Ti 10.5 Nb 12 Ta 12The Hf6 master alloy ingot and the remaining 70% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the fourth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 35 Nb 12 Ta 12 Hf6 master alloy ingot.
[0066] Step 7: Ti 35 Nb 12 Ta 12 The Hf6 master alloy ingot and all Zr metal raw materials are placed in a magnetic levitation induction melting furnace for the fifth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain (TiZr) 70 Nb 12 Ta 12 Hf6 alloy ingot.
[0067] Step 8: (TiZr) 70 Nb 12 Ta 12 The Hf6 alloy ingot is placed in a magnetic levitation induction melting furnace for the sixth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain a uniform composition (TiZr) 70 Nb 12 Ta 12 Hf6 alloy ingot.
[0068] During the above six vacuum melting processes, the voltage of the magnetic levitation induction melting furnace was controlled to be 550 V, the current to be 480 A, the time for each melting was 15 min, the melting vacuum degree was 0.02 Pa, and the argon filling pressure was 0 Pa.
[0069] Step 9: The alloy ingot obtained in step 8 is processed into 10 mm thick discs by wire cutting; then hot rolling is performed at 700 ° C, using multiple hot rolling processes with a total deformation of 80% and a pressing amount of 1.0 mm each time. After the hot rolling, water is used for cooling to obtain (TiZr) 70 Nb 12 Ta 12 Hf6 medium entropy alloy.
[0070] The obtained (TiZr) 70 Nb 12 Ta 12 Hf6 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 80GPa, the yield strength is 554MPa, the tensile strength is 901MPa, and the elongation is 14%. 90The mixing entropy of the Nb4Ta4Hf2 alloy is 1.41R and the valence electron concentration is 4.24.
[0071] Example 3
[0072] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 60 Nb 16 Ta 16 Hf8, wherein each element is expressed in atomic percentage.
[0073] Step 1: Before smelting, the Ti, Zr, Nb, Ta and Hf metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively.
[0074] Step 2: Press (TiZr) 60 Nb 16 Ta 16 The atomic percentage of Hf8 is converted into mass percentage, and the cleaned metal elements of Ti, Zr, Nb, Ta and Hf are accurately weighed to the nearest 0.1 mg.
[0075] Step 3: Place the Nb, Ta and Hf metal raw materials in a magnetic levitation induction melting furnace for the first vacuum melting. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain Nb 16 Ta 16 Hf8 master alloy ingot.
[0076] Step 4: Nb 16 Ta 16 The Hf8 master alloy ingot and 10% Ti metal raw material were placed in a magnetic levitation induction melting furnace for a second vacuum melting. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain Ti3Nb 16 Ta 16 Hf8 master alloy ingot.
[0077] Step 5: Ti3Nb 16 Ta 16 The Hf8 master alloy ingot and 20% Ti metal raw materials were placed in a magnetic levitation induction melting furnace for the third vacuum melting. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain Ti9Nb 16 Ta 16 Hf8 master alloy ingot.
[0078] Step 6: Ti9Nb 16 Ta 16The Hf8 master alloy ingot and the remaining 70% Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the fourth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 30 Nb 16 Ta 16 Hf8 master alloy ingot.
[0079] Step 7: Ti 30 Nb 16 Ta 16 The Hf8 master alloy ingot and all Zr metal raw materials are placed in a magnetic levitation induction melting furnace for the fifth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain (TiZr) 60 Nb 16 Ta 16 Hf8 alloy ingot.
[0080] Step 8: (TiZr) 60 Nb 16 Ta 16 The Hf8 alloy ingot was placed in a magnetic levitation induction melting furnace for the sixth vacuum melting. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a uniform composition (TiZr) 60 Nb 16 Ta 16 Hf8 medium entropy alloy ingot.
[0081] During the above six vacuum melting processes, the voltage of the magnetic levitation induction melting furnace was controlled to be 450V, the current was 460A, the time of each melting was 18 minutes, the melting vacuum was 0.018Pa, and the argon filling pressure was -0.03Pa.
[0082] Step 9: Using wire cutting, the medium entropy alloy ingot obtained in step 8 is processed into a 10 mm thick disc; then hot rolling is performed at 700 ° C, using multiple hot rolling processes, with a total deformation of 80%, and a pressing amount of 1.0 mm each time. After the hot rolling, water is used for cooling to obtain (TiZr) 60 Nb 16 Ta 16 Hf8 medium entropy alloy.
[0083] The obtained (TiZr) 60 Nb 16 Ta 16 Hf8 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 89GPa, the yield strength is 672MPa, the tensile strength is 967MPa, and the elongation is 10%. 60 Nb16 Ta 16 The mixing entropy of the Hf8 alloy is 1.51R and the valence electron concentration is 4.32.
[0084] Example 4
[0085] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0086] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the hot rolling temperature in the ninth step is 800° C. and the total rolling deformation is 80%.
[0087] (TiZr) obtained in this embodiment 90 The arithmetic mean grain size of the Nb4Ta4Hf2 medium entropy alloy is 36µm, and the area-weighted mean grain size is 138µm. -4 / s strain rate test, the results show that the elastic modulus is 74GPa, the yield strength is 464MPa, the tensile strength is 735MPa, and the elongation is 9.8%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0088] Example 5
[0089] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0090] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the hot rolling temperature in the ninth step is 900° C. and the total rolling deformation is 80%.
[0091] (TiZr) obtained in this embodiment 90 The Nb4Ta4Hf2 medium entropy alloy has an arithmetic mean grain size of 130µm and an area-weighted mean grain size of 203µm. -4 / s strain rate test, the results show that the elastic modulus is 71GPa, the yield strength is 378MPa, the tensile strength is 788MPa, and the elongation is 22%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0092] Example 6
[0093] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0094] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the total rolling deformation in the ninth step is 70%.
[0095] The obtained (TiZr) 90 Nb4Ta4Hf2 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 69GPa, the yield strength is 363MPa, the tensile strength is 763MPa, and the elongation is 25%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0096] Example 7
[0097] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0098] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the total rolling deformation in the ninth step is 90%.
[0099] The obtained (TiZr) 90 Nb4Ta4Hf2 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 79GPa, the yield strength is 421MPa, the tensile strength is 831MPa, and the elongation is 18%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0100] Example 8
[0101] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0102] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the proportions of Ti metal raw materials in the fourth, fifth, and sixth steps are 8%, 20%, and 72%, respectively; The obtained (TiZr) 90 Nb4Ta4Hf2 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 72GPa, the yield strength is 380MPa, the tensile strength is 793MPa, and the elongation is 20%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0103] Example 9
[0104] The composition of the multi-principal element low modulus Ti-Zr based medium entropy alloy of this embodiment is (TiZr) 90 Nb4Ta4Hf2, wherein each element is expressed in atomic percentage.
[0105] This embodiment adopts the preparation method of embodiment 1, with the only difference being that the proportions of Ti metal raw materials in the fourth, fifth, and sixth steps are 15%, 25%, and 60%, respectively; The obtained (TiZr) 90 Nb4Ta4Hf2 medium entropy alloy has a 5×10 -4 / s strain rate test, the results show that the elastic modulus is 73GPa, the yield strength is 396MPa, the tensile strength is 812MPa, and the elongation is 23%. 90 The mixing entropy of the Nb4Ta4Hf2 mesoentropy alloy is 1.05R and the valence electron concentration is 4.08.
[0106] Comparative Example 1 The medium entropy alloy composition of this comparative example is (TiZr) 50 Nb 20 Ta 20 Hf 10 , where each element is expressed in atomic percentage.
[0107] Step 1: Before smelting, the Ti, Zr, Nb, Ta and Hf metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively.
[0108] Step 2: Press (TiZr) 50 Nb 20 Ta 20 Hf 10 Convert the atomic percentage into mass percentage, and accurately weigh the clean metal elements of Ti, Zr, Nb, Ta and Hf to the nearest 0.1 mg.
[0109] Step 3: Place the Nb, Ta and Hf metal raw materials in a magnetic levitation induction melting furnace for the first vacuum melting. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain Nb 20 Ta 20 Hf10 Master alloy ingots.
[0110] Step 4: Nb 20 Ta 20 Hf 10 The master alloy ingot and 10% Ti metal raw material are placed in a magnetic levitation induction melting furnace for a second vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti5Nb 20 Ta 20 Hf 10 Master alloy ingots.
[0111] Step 5: Ti5Nb 20 Ta 20 Hf 10 The master alloy ingot and 20% Ti metal raw material are placed in a magnetic levitation induction melting furnace for the third vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 15 Nb 20 Ta 20 Hf 10 Master alloy ingots.
[0112] Step 6: Ti 15 Nb 20 Ta 20 Hf 10 The master alloy ingot and the remaining 70% of the Ti metal raw materials are placed in a magnetic levitation induction melting furnace for the fourth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain Ti 25 Nb 20 Ta 20 Hf 10 Master alloy ingots.
[0113] Step 7: Ti 25 Nb 20 Ta 20 Hf 10 The master alloy ingot and all Zr metal raw materials are placed in a magnetic levitation induction melting furnace for the fifth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain (TiZr) 50 Nb 20 Ta 20 Hf10 ingot.
[0114] Step 8: (TiZr) 50 Nb 20 Ta 20 Hf 10 The ingot is placed in a magnetic levitation induction melting furnace for the sixth vacuum melting. After the melting is completed, the alloy melt is cast into a copper mold and cooled to obtain a uniform composition (TiZr)50 Nb 20 Ta 20 Hf 10 Medium-entropy alloy ingot.
[0115] Step 9: Using wire cutting, the medium-entropy alloy ingot obtained in the eighth step is processed into a 10 mm thick disc; then hot rolling is performed at 700 ° C, using multiple hot rolling passes, with a total deformation of 80%, and a downward pressure of 1.0 mm each time. After the hot rolling is completed, water is used for cooling.
[0116] The obtained (TiZr) 50 Nb 20 Ta 20 Hf 10 Medium entropy alloys at room temperature have a -4 / s strain rate test, the results show that the elastic modulus is 95GPa, the yield strength is 702MPa, the tensile strength is 1034MPa, and the elongation is 9%. 50 Nb 20 Ta 20 Hf 10 The mixing entropy of the medium-entropy alloy is 1.57R and the valence electron concentration is 4.4.
[0117] Comparative Example 2 The alloy composition of this comparative example is Ti 50 Zr 50 , where each element is expressed in atomic percentage.
[0118] Step 1: Before smelting, the Ti and Zr metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying.
[0119] Step 2: Press Ti 50 Zr 50 Convert the atomic percentage into mass, and accurately weigh the clean metal elements of Ti and Zr to the nearest 0.1 mg.
[0120] The third step: Place all the metal raw materials in a magnetic levitation induction melting furnace for vacuum melting. Control the voltage at 550V and the current at 450A for three melting cycles, each melting for 20 minutes. After the melting is completed, cast the alloy melt into a copper mold and cool it to obtain Ti. 50 Zr 50 Alloy ingots.
[0121] Step 4: The alloy ingot obtained in step 8 was processed into 10 mm thick discs using wire cutting. The discs were then hot rolled at 700°C using multiple passes. The total deformation was 80%, and the pressing amount was 0.8 mm each time. The sample temperature became high during each cold rolling process, and water was used for cooling.
[0122] The obtained Ti 50 Zr 50 The alloy is 5×10 -4 The test was carried out at a strain rate of 1 / s, and the results showed that the yield strength was 915 MPa, the tensile strength was 1063 MPa, and the elongation was 6%.
[0123] Figure 2 (TiZr) prepared in Example 1 90 Microstructure of Nb4Ta4Hf2 medium entropy alloy, Figure 3 (TiZr) prepared in Example 4 90 Microstructure of Nb4Ta4Hf2 medium entropy alloy, Figure 4 (TiZr) prepared in Example 5 90 The microstructure of the Nb4Ta4Hf2 medium entropy alloy shows that (TiZr) 90 The microstructure of the Nb4Ta4Hf2 mesoentropy alloy is a single β phase; the arithmetic mean grain size of the alloy is 30~130μm, and the area-weighted mean grain size is 90~210μm; in addition, the hot rolling deformation also has a significant effect on the grain size, thereby presenting different mechanical properties parameters.
[0124] Table 1
[0125] Table 2
[0126] It can be seen from Examples 1 to 3 and Comparative Example 1 that different medium-entropy alloy compositions, mixing entropies and valence electron concentrations are different, thereby making the elastic modulus, yield strength, tensile strength, and elongation of the alloy different. As x increases, mixing entropy, valence electron concentration, elastic modulus, yield strength, tensile strength, etc. all show an increasing trend, while elongation shows a decreasing trend. In addition, as x increases, the raw material price of the alloy will continue to increase. Although the composition of Comparative Example 1 is consistent with the present invention, the atomic percentage of its composition is not within the scope of the present invention, resulting in its elastic modulus being higher and elongation being lower, which does not meet the requirements of the alloy of the present invention. Therefore, in order to make the alloy have a lower elastic modulus and excellent toughness matching performance, and to control cost when designing the alloy, it is necessary to control the atomic percentage of the alloy within a suitable range.
[0127] Combined with Examples 1, 4, and 5, it can be seen that with the change of hot rolling temperature, the elastic modulus, yield strength, tensile strength, and elongation of the alloy fluctuate within a reasonable range; combined with Table 2, the elastic modulus of the alloys prepared in Examples 1, 4, and 5 is ≤74 GPa, and the elongation is ≥9.80%, which shows a low elastic modulus and good elongation.
[0128] From Examples 1, 6, and 7, it can be seen that with the increase in the total hot rolling deformation, the elastic modulus, yield strength, tensile strength, etc. of the alloy show an increasing trend, while the elongation shows a decreasing trend. As shown in Table 2, the elastic modulus (<80 GPa) of the alloys of Examples 1, 6, and 7 is much lower than that of the alloy of the comparative example, and the elongation (≥18%) of the alloys of Examples 1, 6, and 7 is much higher than that of the comparative example.
[0129] It can be seen from Examples 1, 8, and 9 that the Ti metal raw material is melted three times during the smelting process, gradually lowering the melting point of the alloy and obtaining an alloy ingot with uniform chemical composition, so that the alloy has a lower elastic modulus and excellent elongation.
[0130] Combined with Table 2, it can be seen that the elastic modulus of the multi-principal element low-modulus Ti-Zr-based medium-entropy alloys prepared in Examples 1 to 9 is 69 to 90 GPa, the yield strength is 363 to 672 MPa, the tensile strength is 735 to 967 MPa, the elongation is 9.8% to 25%, the mixing entropy is 1.05 to 1.51R, and the valence electron concentration is 4.08 to 4.32. Compared with Comparative Examples 1 and 2, the medium-entropy alloys prepared in the examples of the present invention have a lower elastic modulus and good elongation, taking into account the lower elastic modulus and excellent strength-toughness matching.
[0131] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, and all of these should be included in the scope of the claims of the present invention.
Claims
1. A multi-principal element low modulus Ti-Zr based medium entropy alloy, characterized in that: Its composition in atomic percentage is (TiZr) 100-10x Nb 4x Ta 4x Hf 2x , where 1≤x≤4.
2. The multi-principal element low modulus Ti-Zr based medium entropy alloy according to claim 1, characterized in that: The multi-principal element low modulus Ti-Zr based medium entropy alloy is (TiZr) 90 Nb4Ta4Hf2、(TiZr) 80 Nb8Ta8Hf4、(TiZr) 70 Nb 12 Ta 12 Hf6、(TiZr) 60 Nb 16 Ta 16 At least one of Hf8.
3. The multi-principal element low modulus Ti-Zr based medium entropy alloy according to claim 1, characterized in that: The multi-principal element low modulus Ti-Zr based medium entropy alloy has a single-phase body-centered cubic crystal structure, and its microstructure is a single β phase.
4. The multi-principal element low modulus Ti-Zr based medium entropy alloy according to claim 1, wherein: The mixing entropy of the multi-principal element low modulus Ti-Zr-based medium entropy alloy is 1R~1.6R, and the valence electron concentration is 4~4.
5.
5. The multi-principal element low modulus Ti-Zr based medium entropy alloy according to claim 1, characterized in that: The multi-principal element low-modulus Ti-Zr-based medium-entropy alloy has an elastic modulus of 65-90 GPa, a yield strength of 350-700 MPa, a tensile strength of 730-1000 MPa, and an elongation of 9.5%-25%.
6. A method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, after pre-treating the Ti, Zr, Nb, Ta, and Hf metal raw materials, weighing the metal raw materials according to the atomic percentage of the Ti-Zr-based medium entropy alloy; S2, performing a first vacuum melting of the Nb, Ta, and Hf metal raw materials to obtain a NbTaHf master alloy ingot; S3, vacuum melting the Ti metal raw material and the NbTaHf master alloy ingot three times to obtain a NbTaHfTi master alloy ingot; S4, the Zr metal raw material and the NbTaHfTi master alloy ingot are vacuum melted for the fifth time to obtain (TiZr) 100- 10x Nb 4x Ta 4x Hf 2x Alloy ingot, where 1≤x≤4; S5, (TiZr) 100-10x Nb 4x Ta 4x Hf 2x The alloy ingot is vacuum melted for the sixth time. After melting, the alloy melt is cast into a water-cooled copper mold. After cooling, a uniform composition (TiZr) is obtained. 100-10x Nb 4x Ta 4x Hf 2x alloy ingots; S6, the (TiZr) obtained in step S5 100-10x Nb 4x Ta 4x Hf 2x The alloy ingot is processed into an alloy plate after cooling, and then the alloy plate is subjected to multiple hot rolling treatments at high temperature. After each hot rolling treatment, it is cooled with water to obtain a multi-principal element low modulus Ti-Zr based medium entropy alloy.
7. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: In step S1, the pretreatment includes pickling, ethanol cleaning under ultrasonic conditions, and vacuum drying.
8. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: In step S1, the Ti, Zr, Nb, Ta, and Hf metal raw materials are all metal single-substance particles, the purity of the metal single-substance particles is ≥99.5%, and the size of the metal single-substance particles is 2-10 mm.
9. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: During the vacuum melting process in steps S2 to S5, a magnetic levitation induction melting furnace is used, and the voltage of the magnetic levitation induction melting furnace is controlled to be 360 to 550 V, the current is 450 to 480 A, the time of each melting is 15 to 20 minutes, the melting vacuum is 0.016 to 0.02 Pa, and the argon filling pressure is -0.06 to 0 Pa.
10. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: In step S2, the atomic percentage of the NbTaHf master alloy ingot is Nb2Ta2Hf1.
11. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: The specific process of step S3 is as follows: Ti metal raw materials were divided into three batches according to mass percentage: 8-15%, 20-25% and 60-72%; The Ti metal raw material containing 8-15% and the NbTaHf master alloy ingot are vacuum melted for the second time to obtain a master alloy ingot A; The 20-25% Ti metal raw material and the master alloy ingot A are vacuum melted for the third time to obtain the master alloy ingot B; The remaining 60-72% of the Ti metal raw material and the master alloy ingot B are vacuum melted for the fourth time to obtain a NbTaHfTi master alloy ingot.
12. The method for preparing a multi-principal component low modulus Ti-Zr based medium entropy alloy according to claim 6, wherein: In step S6: The thickness of the alloy plate is 10-30 mm; During the multi-pass hot rolling process, the hot rolling temperature is 700-900° C., the total hot rolling deformation is 70%-90%, and the pressing amount of each pass is 1.0-2.0 mm.
Citation Information
Patent Citations
Biomedical Ti-Zr-Hf-Nb-Ta series high-entropy alloy and preparing method
CN110423933A
Low-modulus high-ductility Ti-Zr high-entropy alloy and preparation method and application thereof
CN118048569A
Preparation method of medium-high entropy alloy material
CN112916870A
Five-element intermediate alloy material and preparation method and application thereof
CN112941393A
Medical high-toughness tantalum-containing medium-entropy alloy and preparation method thereof
CN118256790A